Preoperative walking intervention did not appear to improve patient-reported postoperative recovery in older adults with frailty traits: Randomized trial. Issue 38 (23rd September 2022) - Sadiq, Hammad; Rampam, Sanjeev; Patel, Jay; Crawford, Sybil; Walz, Matthias; Kapoor, Alok
Abstract : Objectives: To assess the impact of a preoperative walking intervention on improving postoperative recovery in at-risk frail older adult patients. Study Type: Unblinded, randomized controlled trial which assigned patients to intervention versus control. Population: Patients aged 60+ scheduled for surgery 3–8 weeks from randomization scoring 4+ on the Edmonton Frail Scale. Intervention: Preoperative walking enhanced by goal setting with an activity monitor and telephonic coaching. Main Outcomes: Quality of Recovery 9-item instrument total score and a modified version of the Abdominal Surgery Impact Scale total score Results: A total of 83 patients were analyzed. Postoperative recovery scores were similar in intervention vs control – Quality of Recovery-9 item instrument total score 14.1 vs. 14.1 ( P = .94) and modified Abdominal and Surgery Impact Scale total score 82.8 vs. 79.2 ( P = .93). Few intervention patients met their daily step count goals. Despite this, intervention patients improved average daily step counts significantly. Conclusions: Preoperative walking bolstered with activity monitor and remote coaching did not appear to lead to improved postoperative recovery in older adults with frailty traits. Further research is necessary to see if a similar intervention in specific surgery types or a more intense version of the intervention can improve recovery.